A tool to draw chemical equilibrium diagrams using SIT: Applications to geochemical systems and radionuclide solubility. Issue 1665 (2014) - Puigdomènech, I.; Colàs, E.; Grivé, M.; Campos, I.; García, D.
ABSTRACT: A set of computer programs has been developed to draw chemical-equilibrium diagrams. This new software is the Java-language equivalent to the Medusa/Hydra software (developed some time ago in Visual basic at the Royal Institute of Technology, Stockholm, Sweden). The main program, now named "Spana" calls Java programs based on the HaltaFall algorithm. The equilibrium constants that are needed for the calculations may be retrieved from a database included in the software package ("Database" program). This new software is intended for undergraduate students as well as researchers and professionals. The "Spana" code can be easily applied to perform radionuclide speciation and solubility calculations of minerals, including solubility calculations relevant for the performance assessment of a nuclear waste repository. In order to handle ionic strength corrections in such calculations several approaches can be applied. The "Spana" code is able to perform calculations based on three models: the Davies equation; an approximation to the model by Helgeson et al. (HKF); and the Specific Ion-Interaction Theory (SIT). Default SIT-coefficients may be used, which widens the applicability of SIT significantly. A comparison is made here among the different ionic strength approaches used by "Spana" (Davies, HKF, SIT) when modelling the chemistry of radionuclides and minerals of interest under the conditions of a geological repository for nuclear waste. For this purpose, amorphous hydrous Thorium(IV) oxide (ThO2 (am)), Gypsum (CaSO4 ·2H2 O) and Portlandite (Ca(OH)2 ) solubility at high ionic strengths have been modelled and compared to experimental data from the literature. Results show a good fitting between the calculated values and the experimental data especially for the SIT approach in a wide range of ionic strengths (0-4 M).